2022
DOI: 10.3390/ijerph191610368
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness Assessment by Pulse Wave Velocity in Patients with Metabolic Syndrome and Its Components: Is It a Useful Tool in Clinical Practice?

Abstract: Metabolic syndrome (MS) is not a single disease but a cluster of metabolic disorders associated with increased risk for development of diabetes mellitus and its complications. Currently, the definition of MS published in 2009 is widely used, but there are more versions of the diagnostic criteria, making it difficult to conduct scientific discourse in this area. Increased arterial stiffness (AS) can predict the development of cardiovascular disease both in the general population and in patients with MS. Pulse w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 129 publications
2
33
0
Order By: Relevance
“…A strong association between metabolic syndrome and oxidative stress has been found [ 31 ]. Enhanced oxidative stress is closely related to increased body mass index, blood pressure, and triglycerides [ 32 , 33 ]. Moreover, ‘obesity and insulin resistance’ are the components of metabolic syndrome, which are most strongly associated with metabolic syndrome [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong association between metabolic syndrome and oxidative stress has been found [ 31 ]. Enhanced oxidative stress is closely related to increased body mass index, blood pressure, and triglycerides [ 32 , 33 ]. Moreover, ‘obesity and insulin resistance’ are the components of metabolic syndrome, which are most strongly associated with metabolic syndrome [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic oxidative stress plays a major role in resulting insulin resistance and hyperglycemia [ 31 ]. Furthermore, an elevation of carotid arterial stiffness and a risk of cardiovascular disease are closely associated with metabolic syndrome through a pathway of oxidative stress [ 33 , 35 ]. Because oxidative stress and cardiovascular diseases are known to be elevated in sarcopenia [ 36 , 37 ], metabolic syndrome under the condition of sarcopenia should be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the prevalence of MetS among the age-standardized group was reported as 17.8% in females and 9.8% in males [ 9 , 10 ]. A previous study indicated that MetS is linked to the developing of T2DM and its complications [ 11 ]. In addition, a recent survey indicated that the prevalence of MetS in the T2DM groups was 73.5% in males and 75.4% in females [ 12 ].Therefore, growing evidence suggests that it is essential to identify the modifiable risk factors to delay the progression of MetS.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress represents a significant role in the development and progression of each MetS component and other related complications such as endothelial dysfunction, arterial stiffness, and adipose tissue dysfunction, perpetuating the cycle of multiorgan damage [ 1 , 5 ]. Arterial stiffness is a marker of subclinical vascular damage and a predictor for CVD in patients with MetS [ 5 , 6 ]. SBP and DBP are directly linked to arterial stiffness; moreover, this can be assessed through the measurement of pulse wave velocity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arterial stiffness is a marker of subclinical vascular damage and a predictor for CVD in patients with MetS [ 5 , 6 ]. SBP and DBP are directly linked to arterial stiffness; moreover, this can be assessed through the measurement of pulse wave velocity [ 6 ]. Adipose tissue dysfunction also has an important contribution to MetS and subsequent complications [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%